Antioxidant and antimicrobial properties of Artocarpus lakoocha leaves and heartwood for natural food preservative - Pumriw, Supaporn; Huaisan, Kannika; Nitisuk, Panorjit; Bhumsaidon, Apinya; Sangsopha, Jintana; Pranil, Thorung (Food Agricultural Sciences and Technology, 2024)
Artocarpus lakoocha Roxb. (Moraceae) is highly regarded for its properties. The bioactive composition (total phenolic and ﬂavonoid contents) of A. lakoocha leaves and heartwood extracts, as well as the antioxidant activity against 2,2-Diphenyl-1-picrylhydrazyl (DPPH), were evaluated. Furthermore, the antibacterial properties of these extracts were evaluated against strains of Escherichia coli (E. coli), Bacillus subtilis (B. subtilis), Bacillus cereus (B. cereus), Staphylococcus aureus (S. aureus), and Salmonella typhimurium (S. typhimurium). Our study showed that the heartwood extracts had high total phenolic content (53.93 mg GAE/g dry extract), total ﬂavonoid content (1459.73 µg QE/g dry extract), and strong antioxidant activity (119.37 µg Vitamin C/g dry extract). The antibacterial results also demonstrated that the heartwood extracts showed a maximum inhibition zone of 15.55 mm against B. cereus. While the leaf extracts’ inhibitory zone against B. cereus was 4.86 mm. Both extracts were sensitive to gram-negative bacteria (E. coli) with the lowest minimum inhibitory concentration (MIC) (1.953 mg/mL). However, the extracts were insensitive to S. typhimurium, with the highest MIC value of 125 mg/mL and 3.906 mg/mL from leaves and heartwood extracts respectively. The result’s fndings underscore the bioactive composition, antioxidant capacity, and antimicrobial properties of A. lakoocha heartwood extract, suggesting its potential as a possible natural antibacterial source for food preservation applications.